Magnetic Anomaly Characteristics and Prospects in Xiaoguanhe-Hekou Area of Huili, Sichuan Province - Weizhong ZUO; Yingdong LIU; Tao CHEN; Hongqing LIU; Li XU; Zhimin ZHU (Kuangchan zonghe liyong)
The Xiaoguan-Hekou area in Huili, Sichuan Province is located in the middle of the Kangdian axis in the western margin of the Yangtze Platform, which is an important South-North Cu-polymetallic metallogenic belt of Sichuan and Yunnan, with abundant mineral resources. Thirty-one magnetic anomalies were delineated by using the 1∶50 000 high-precision surface magnetic survey, 16 of which are of further prospecting significance, mainly concentrated in the area of Baiyun Mountain, Dayun Mountain, Lushui and Lijiafen in the Pingdi geological map, the Zhongchang, Maoguba area on the Hekou geological map and the Yanghe and Xinfa areas in the northeast in the Xiaoguanhe geological map, the areas of Yanghewu, Hongshijing, Jianshan, Daheiyi, Caiziyuan, Guancun, Dacun in the southwest and Agulu, Shimenkan in the southeast. This provides very important information for the further geological exploration in the area.